The Progress of the EU Labor Market Based on the Green Economy - ALINA LIGIA DUMITRESCU (Global Economic Observer)
The article focuses on the analysis of the challenges and opportunities of the labour market in the conditions of the transition to the climate-neutral economy. The research methodology is based on the research of specialized literature in the field about green transition and the comparative analysis of the data on green jobs from International Renewable Energy Agency, International Labour Organisation and Eurostat. The key objective of the research is to identify the main qualifications necessary to increase employment in green economy and means to accelerate the implementation process of transition to a climate-neutral economy in the European Union. In conclusion, in the context of the cohesion policy, the specific challenges of the European Union are to strengthen the economic, social, and territorial cohesion based on the Union’s political priorities according to the green and digital transition.